Pengembangan Aplikasi Sistem Informasi Geografis Berbasis Web untuk Manajemen Data Sekolah di Denpasar Menggunakan Arsitektur Microservice - Ni Made Ardhiya Shita Pramesti Dewi; Putu Prianka Vedanty; I Nyoman Sugiarta (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research discusses the development of a school Geographic Information System (GIS) based on a microservice architecture to simplify access and management of school data. The background of this study is the need for an efficient and well-organized school data management system that can present school information interactively to the public. The purpose of this research is to build a system capable of displaying school locations and providing data management features for teachers, students, and school accreditation through CRUD (Create, Read, Update, Delete) operations. The development method includes database design, API creation for each microservice, data integration through an interactive map interface using Leaflet, and system testing using the Black Box Testing method. The test results show that all system features function properly and meet user requirements. The implementation of microservice architecture allows the system to be more flexible, easily updated, and well distributed among services. With this system, the public can access school information quickly and accurately, while schools can manage their data more effectively.